Identification of identical twins in police procedures - Dvojmoč, Miha (Varstvoslovje, 2022)
Purpose: The aim of the study was to review the treatment of identical twins in crimes and to determine to what extent people notice the switch of identities, to what extent they can distinguish between twins, and what factors are related to the ability to distinguish them. Design/Methods/Approach: We carried out an analysis of literature and a case review about identification of identical twins in police procedures and for the purpose of the article, an online survey was conducted among the general public. Findings: In line with existing research, the survey showed that age, but not gender or length of acquaintance, was related to the ability to distinguish between twins. The ability to distinguish between twins is positively correlated with the observation of confusion between them. Our survey of the public found that the most common indicators for distinguishing between identical twins were facial features, behavior, a distinctive voice, and recognizable accessories. Research Limitations/Implications: A review of the literature on the identification and treatment of twins in relation to criminality reveals several gaps in knowledge. More attention should thus be paid to the problem in the future, possibly to establish criteria for prosecution and to raise awareness that such deviant behavior can occur. In our research, we conducted survey among general public in the future maybe a survey of the experts should be conducted for more comprehensive view of the issue. Among the proposals for further research, it would be reasonable to consider the analysis of cases of identical twins in police practice. Originality/Value: In our own research, we examined the factors associated with identity swapping among identical twins.
Keywords: distinction; enojajčni dvojčki; fraud; goljufanje; identical twins; identity switch; ločevanje; zamenjava identitete